Embracing a technologically enhanced environment: Postgraduate students’ learning experiences in mobile learning platform - Thiagraj, Malini; Abdul Karim, Abdul Malek (ISRA, 2020)
The purpose of this study is to identify the postgraduate students’ Mobile learning (M-learning) experiences in Massive Open Online Courses (MOOCs) as a platform. Learning logbook is used to measure the students’ real-time learning experiences in Future Learn (FLMOOC) which is one of the learning platforms in MOOCs. This study is qualitative in nature and employed thematic analysis. This study used the purposive sampling method in choosing 34 postgraduate students in one of the public universities in Malaysia. These postgraduate students were introduced to FutureLearn (MOOCs) platform. Daily and weekly based learning logbook were distributed to the students’ to express their experiences. Data were analysed using the thematic analysis method. The themes derived is device used and online course elements. Most of the students’ were not aware on Mlearning platform and students’ technology skills enhanced after gained actual learning experiences using own mobile devices for conclusive online course elements.